Soft Skill Integration, Quality Of College Life And Soft Skill Levels In Malaysian Private Higher Learning Institutions - Tan, Cheng Yoke (2018)
This study aimed to investigate the relationship between soft skill integration, quality of college life and perceived soft skill levels of the Diploma Business students in Malaysian private higher learning institutions (IPTS). It was grounded on Astin’s Input-Environment-Output Model (1984) and Malaysian MOHE Soft Skill Development Model (2006). This study used quantitative survey method to obtain the data. A total of 429 final year diploma business students from 12 different IPTS from three states of Peninsular Malaysia responded to the questionnaires through stratified random sampling method. The study conducted data analysis by finding the mean average descriptive data, regression analysis and hierarchical moderated multiple regression. The results showed that soft skill integration in teamwork (x̅ = 3.71), integration in ethics and professional moral (x̅ = 3.75) were high. However, only the levels of teamwork (x̅ = 3.72) was high. Besides that, the academic aspects of quality of college life did significantly influence the development of all soft skill levels. The findings advocated to the importance of soft skill integration on soft skill development, especially the integration on critical thinking and problem solving and its levels. The colleges could also upgrade the facilities as the results indicated some moderating influence from facility aspects of quality of college life. These findings highlighted the right focus, effective practices to promote soft skill development in order to bridge the soft skill gaps and tackle employability issues of current graduates. Subsequently, it provided empirical data to the relevant authorities such as Malaysian Ministry of Higher Education, Malaysian Qualification Agency as well as the management of higher learning institutions in future policy making and direction in educational aspirations or endeavour in future.